Role of urinary nitrites in predicting steroid responsiveness of nephrotic syndrome: a study conducted in tertiary care center - Kodandapani, Yerroju; Varahala, Ajay Mohan; Songa, Rajesh Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: Nephrotic Syndrome (NS) is a common chronic disorder, characterized by alterations of selective permeability at the glomerular capillary wall, resulting in its inability to restrict the urinary loss of protein. Urinary nitrite excretion serves as a useful investigation in differentiating between steroid responsive and steroid resistant nephrotic syndrome. The aim of the study was to assess the relation between urinary nitrite levels and steroid responsiveness in nephrotic syndrome in children. Methods: 76 children were enrolled in the study suffering with nephrotic syndrome of which 58 children were Steroid Sensitive (SSNS) and 18 were Steroid Resistant (SRNS). 25 children were enrolled as controls. The urinary nitrites were estimated in these subjects and the results were analyzed. Results: All the control subjects were tested negative for urinary nitrites. After achieving remission with steroids, out of 58 SSNS subjects’ 27 subjects tested positive for urinary nitrites, remaining 31 tested negatives for the same. Of the 18 SRNS subjects 1 subject tested positive for urinary nitrites remaining 17 subjects were tested negative for the same. Conclusions: The findings of present study suggest that urinary nitrite excretion is increased in patients with steroid responsive nephrotic syndrome. The urinary nitrite estimation has low NPV and high PPV in predicting steroid responsiveness.